Mesoporous Silica Nanoparticles‐Reinforced Hydrogel Scaffold together with Pinacidil Loading to Improve Stem Cell Adhesion. Issue 7 (24th May 2018) - Wang, Ning; Ma, Ming; Luo, Yu; Liu, Tianzhi; Zhou, Peng; Qi, Shengcai; Xu, Yuanzhi; Chen, Hangrong
Abstract: Although hydrogels can be applied in mimicking the native extracellular matrix environment, they generally suffer from weak mechanical properties, as well as the lack of a sustained supply of nutrients or simulants to maintain cell functions, which severely limits their further practical applications. Aiming to address the aforementioned issues, a novel reinforced nanocomposite hydrogel (NC gel) is developed, which is composed of gelatin methacryloyl (GelMA) and carboxyl‐modified mesoporous silica nanoparticles (MSNs‐COOH) together with pinacidil loading. The mechanical properties and pore size of the NC gel can be tunable with the addition of different amounts of MSNs‐COOH. In addition, mesoporous channels of MSNs‐COOH endow the prepared NC gel with good performance in piancidil loading and long‐term sustained release, which greatly promotes the viability and adhesion of bone marrow mesenchymal stem cells (BMSCs) and achieves the long‐term cell adhesion, spreading and viability of encapsulated BMSC cells in 7 days. This NC gel platform shows great promise for tissue engineering applications, including functional integration and efficient differentiation of stem cells upon transplantation. Abstract : Carboxyl‐modified mesoporous silica nanoparticles on a reinforced hydrogel scaffold were used together with pinacidil loading to improve stem cell adhesion.